Eksplorasi Spesies Gastropoda Air Tawar di Perairan Siring Agung Kota Lubuklinggau - Nura Maziyyatul Izza; Sifa`u Rahmah; Riska Rahmadhani; Penti Fidiana; Enjellica Dwi Ariyani; Dian Samitra (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
Gastropods are one of the animals used as bioindicators of aquatic environmental quality. The presence and abundance of gastropods can reflect the condition of an ecosystem, while low numbers may indicate disturbances or changes in habitat quality. This study aims to identify the species of freshwater gastropods found in the Siring Agung Waters, Lubuklinggau City. The research method used was a survey method involving direct sampling at predetermined locations. Species identification was based on the morphological characteristics of the organisms found in the field. The results of the study indicate that four species of freshwater gastropods were found in the Siring Agung Waters, namely the apple snail (Pomacea canaliculate), the African giant snail (Achatina fulica), the Javanese pond snail (Filopaludina javanika), and the Melanoides sp.